Highly water-absorbent resin composition and method for producing same
Patent Information
- Application Number
- JP2024548650
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-03-23
- Filing Date
- 2023-03-24
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-03-24
AI Technical Summary
【0011】 上述のように、本発明は、高吸水性樹脂に特定の添加剤を組み合わせて使用することによって、優れた消臭力を有し、菌の成長を抑制して追加的な悪臭の発生を抑制させた高吸水性樹脂組成物および製造方法を提供することを特徴とする。
Smart Images

Figure 2025506240000001 
Figure 2025506240000002 
Figure 2025506240000003
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0039062 filed on March 29, 2022 and Korean Patent Application No. 10-2023-0038011 filed on March 23, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to a superabsorbent polymer composition and a method for producing the same, and more particularly to a superabsorbent polymer composition that, by using a combination of specific additives, has improved deodorizing and anti-odor properties and, when applied to products such as diapers, effectively suppresses odors generated from urine and the like and the growth of bacteria that occurs while the products are being worn, and a method for producing the same. [Background technology]
[0003] Super absorbent polymer (SAP) is a synthetic polymeric substance that has the ability to absorb 500 to 1,000 times its own weight in water, and each developer has given it a different name, such as SAM (Super Absorbency Material) or AGM (Absorbent Gel Material). Such super absorbent polymers first came into practical use as sanitary products, and are now widely used in a wide range of applications, including sanitary products such as disposable diapers for babies, soil water retention agents for gardening, water stoppers for civil engineering and construction, seedling sheets, freshness preserving agents in the food distribution field, and materials for packs.
[0004] In most cases, such superabsorbent polymers are widely used in the field of sanitary materials such as diapers and sanitary napkins. In such sanitary materials, the superabsorbent polymer is generally contained in a dispersed state in the pulp. However, in recent years, efforts have been made to provide sanitary materials such as diapers with thinner thicknesses, and as part of such efforts, the pulp content has been reduced or, going a step further, the development of so-called pulpless diapers in which no pulp is used at all has been actively promoted.
[0005] In this way, in the case of sanitary materials in which the pulp content is reduced or no pulp is used, the superabsorbent resin is contained at a relatively high ratio, and such superabsorbent resin particles are inevitably contained in multiple layers in the sanitary materials. In order for the overall superabsorbent resin particles contained in multiple layers to more efficiently absorb liquids such as urine, the superabsorbent resin must basically exhibit high water absorption performance and water absorption speed. In addition, the absorbed liquid must be able to escape even under external pressure, and in addition, permeability is required to maintain the original shape well even when absorbing liquid and swelling. Therefore, many studies have been conducted, such as surface cross-linking, to improve the basic water absorption and water retention of superabsorbent resins.
[0006] On the other hand, highly absorbent polymers are used in sanitary materials such as diapers and sanitary napkins, and in these cases, there is a problem that the unpleasant odor of absorbed liquids such as human and pet excrement deteriorates the comfort of use. In addition, there is also a problem that the growth of bacteria accelerates over time, causing a bad odor.
[0007] In addition to the basic physical properties of superabsorbent resins, such as water absorption and water retention, there is a gradually increasing demand for suppression of malodors. Therefore, there is a need to produce superabsorbent resins that have deodorizing power and can effectively suppress the growth of bacteria. Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention provides a superabsorbent polymer composition and a method for producing the same. More specifically, the present invention provides a superabsorbent polymer composition that effectively suppresses odors such as urine and the growth of bacteria when applied to products such as diapers by improving deodorizing and anti-odor capabilities through the use of a combination of specific additives, and a method for producing the same. [Means for solving the problem]
[0009] In order to solve the above problems, the present invention provides the following superabsorbent polymer composition: A superabsorbent resin comprising: a base resin including a crosslinked polymer obtained by crosslinking an acrylic acid monomer having at least a partially neutralized acidic group with an internal crosslinking agent; and a surface crosslinked layer formed on the surface of the base resin, the surface crosslinked layer being further crosslinked with the crosslinked polymer via a surface crosslinking agent; Aminoacetate chelating agents; and Cysteine; The aminoacetate-based chelating agent and cysteine are each independently contained inside the surface-crosslinked layer or on the surface of the surface-crosslinked layer.
[0010] The present invention also provides the following method for producing a superabsorbent polymer composition: Step 1: forming a hydrogel polymer by cross-linking and polymerizing an acrylic acid monomer having at least a part of neutralized acid groups in the presence of an internal cross-linking agent and a polymerization initiator; A step (step 2) of preparing a base resin containing a crosslinked polymer by drying and pulverizing the hydrogel polymer; mixing the base resin with a surface cross-linking composition to produce a mixture (Step 3); and Step 4: heat-treating the mixture to produce a superabsorbent resin having a surface cross-linked layer formed on the surface of the base resin; The aminoacetate-based chelating agent and cysteine are mixed independently in at least one of steps 2 to 4 and steps before and after these steps. Effect of the Invention
[0011] As described above, the present invention is characterized by providing a superabsorbent polymer composition and a manufacturing method thereof, which have excellent deodorizing power and inhibit the growth of bacteria and the generation of additional malodors by using a specific additive in combination with a superabsorbent polymer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention.
[0013] The singular expression includes the plural expression unless the context clearly indicates otherwise. It should be understood that, in this specification, the terms "comprise", "comprise", "have" and the like are intended to specify the presence of embodied features, steps, components, or combinations thereof, and do not preclude the possibility of the presence or addition of one or more other features, steps, components, or combinations thereof.
[0014] The terms first, second, third, etc. are used to describe various elements, and such terms are used only to distinguish one element from another.
[0015] The term "polymer" or "polymeric polymer" as used herein means a state in which a water-soluble ethylenically unsaturated monomer is polymerized, and may include any range of water content or particle size. Among the above polymers, a polymer having a water content (water content) of about 40% by weight or more in a state after polymerization and before drying may be called a hydrogel polymer, and particles of such a hydrogel polymer that have been crushed and dried may be called a crosslinked polymer.
[0016] In addition, the term "base resin" or "base resin powder" refers to a polymer obtained by drying and pulverizing a polymer in which an acrylic acid monomer is polymerized into particles or powder, and means a polymer in a state in which the surface modification or surface crosslinking step described below has not been performed.
[0017] Furthermore, the term "super absorbent polymer" or "super absorbent polymer powder" refers to, depending on the context, a crosslinked polymer obtained by polymerizing a water-soluble ethylenically unsaturated monomer (acrylic acid monomer) containing acidic groups and at least a portion of the acidic groups being neutralized, or a powder-like base resin consisting of super absorbent polymer particles obtained by pulverizing the crosslinked polymer, or is used to encompass all of the crosslinked polymers or base resins that have been subjected to additional processes, such as surface crosslinking, fine powder regranulation, drying, pulverization, classification, etc., to be in a state suitable for commercialization.
[0018] Although the present invention can be modified in various ways and has various forms, specific embodiments are exemplified and described in detail below. However, it is not intended to limit the present invention to the specific disclosed embodiments, and it should be understood that the present invention includes all modifications, equivalents, and alternatives falling within the spirit and technical scope of the present invention.
[0019] Hereinafter, the method for producing a superabsorbent polymer and the superabsorbent polymer will be described in more detail with reference to specific embodiments of the present invention.
[0020] (Super absorbent resin composition) According to one embodiment of the present invention, a superabsorbent polymer composition is provided.
[0021] The superabsorbent resin composition includes a superabsorbent resin including a base resin including a crosslinked polymer obtained by crosslinking an acrylic acid monomer having at least a partially neutralized acidic group with an internal crosslinking agent, and a surface crosslinked layer formed on the surface of the base resin and obtained by additionally crosslinking the crosslinked polymer via a surface crosslinking agent; an aminoacetate chelating agent; and cysteine; The aminoacetate-based chelating agent and cysteine are each independently contained inside the surface-crosslinked layer or on the surface of the surface-crosslinked layer.
[0022] Superabsorbent polymers are widely used in sanitary materials such as diapers and sanitary napkins, but the unpleasant odor of human and pet excrement can reduce the comfort of use. In addition, liquids absorbed by the product can accelerate the growth of bacteria over time, resulting in additional odors.
[0023] In the past, when deodorizing substances were included in products to reduce odors, they had to be used in excess to achieve the desired level of deodorizing power, which resulted in a significant decrease in water absorption properties and increased product costs.
[0024] The inventors have discovered that by using a combination of specific additives, it is possible to effectively control odors caused by a variety of factors without reducing the basic physical properties of superabsorbent resins, namely, their water absorption and water retention, and have thus completed the present invention.
[0025] Specifically, according to the present invention, when the product is applied, it is possible to effectively control both the primary odor caused by odor-generating substances contained in body fluids, urine, etc., and the secondary odor caused by bacterial growth. Furthermore, the combined use of the two additives makes it possible to realize excellent deodorizing and anti-odor capabilities with a relatively small amount, which is economical, and is particularly preferable since it does not reduce water absorption properties.
[0026] The aminoacetate chelating agent is an ingredient that can effectively inhibit the growth of bacteria such as E. coli that are generated by malodorous substances. As time passes while wearing the product, the growth of bacteria accelerates due to the malodorous substances remaining in the product, which generates additional malodorous odors. However, the aminoacetate chelating agent can inhibit the growth of such bacteria and effectively reduce the generation of additional malodorous odors.
[0027] In particular, aminoacetate chelating agents are divalent cations that form salt bridges between cell membrane components, and can effectively inhibit bacterial growth by destroying bacterial cell membranes.
[0028] The aminoacetate-based chelating agent may include, for example, one or more selected from the group consisting of ethylenediaminetetraacetic acid (EDTA), L-glutamic acid diacetate (GLDA), methylglycine diacetate (MGDA), hydroxyethylethylenediaminetriacetic acid (HEDTA), ethanol diglycine acid (EDG), diethylenetriaminepentaacetic acid (DTPA), and salts thereof.
[0029] The aminoacetate-based chelating agent is contained in an amount of 0.01 to 3 parts by weight, and preferably 0.025 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, 2.5 parts by weight or less, 2.0 parts by weight or less, 1.5 parts by weight or less, or 0.01 to 2.5 parts by weight, 0.01 to 2.0 parts by weight, 0.025 to 3.0 parts by weight, 0.025 to 2.5 parts by weight, 0.05 to 2.5 parts by weight, 0.05 to 2.0 parts by weight, 0.1 to 2.5 parts by weight, or 0.1 to 2.0 parts by weight.
[0030] When used within the above content range, bacteria can be effectively inhibited without reducing the water absorption properties, and the deodorizing and odor preventing properties of the water absorbent resin can be significantly improved. The chelating agent can be used by mixing with an aqueous solution in the form of a salt, and therefore the above content range is based on the solid content. On the other hand, when the chelating agent is contained in a small amount, the desired degree of bacteria inhibition property cannot be achieved, and when contained in an excessive amount, the inherent properties of the superabsorbent resin may be reduced.
[0031] The cysteine can chemically react with substances that generate malodors to reduce the malodors. Substances that generate malodors generally have small molecular weights, and when they react with cysteine, the malodors are reduced or removed, so that the malodors can be effectively suppressed. In particular, cysteine is effective in reducing the malodors generated by aldehyde and ketone compounds. Meanwhile, when methionine or the like is used as a similar amino acid, it can show some deodorizing power, but the main functional groups are different, and even if the same amount is applied to SAP, the water absorption properties and deodorizing power may be significantly reduced compared to cysteine.
[0032] The cysteine is contained in an amount of 0.01 to 3 parts by weight, relative to 100 parts by weight of the base resin, and preferably 0.025 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, 2.5 parts by weight or less, 2.0 parts by weight or less, 1.5 parts by weight or less, or 0.01 to 2.5 parts by weight, 0.01 to 2.0 parts by weight, 0.025 to 3.0 parts by weight, 0.025 to 2.5 parts by weight, 0.05 to 2.5 parts by weight, 0.05 to 2.0 parts by weight, 0.1 to 2.5 parts by weight, or 0.1 to 2.0 parts by weight.
[0033] When used within the above content range, it is possible to effectively suppress the generation of malodors without reducing the water absorption properties, and to significantly improve the deodorizing and odor preventing properties of the water absorbent resin. The cysteine can be used by mixing it with an aqueous solution in the form of a salt, and therefore the above content range is based on the solid content. On the other hand, when the cysteine is contained in a small amount, the deodorizing properties are not realized, and when it is contained in an excessive amount, the inherent properties of the superabsorbent resin are reduced and there may be a problem in the process due to incomplete dissolution.
[0034] The base resin includes a crosslinked polymer obtained by crosslinking an acrylic acid monomer having at least a partially neutralized acid group with an internal crosslinking agent.
[0035] The acrylic acid monomer may be any monomer commonly used in the manufacture of superabsorbent resins. Specifically, the acrylic acid monomer may be a compound represented by the following formula 1:
[0036] [Chemical formula 1] R 1 -COOM 1
[0037] In the above Chemical Formula 1, R 1 is an alkyl group having 2 to 5 carbon atoms and containing an unsaturated bond, M 1 is a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.
[0038] Preferably, the acrylic acid monomer includes at least one selected from the group consisting of acrylic acid, methacrylic acid, and their monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts.
[0039] The acrylic acid monomer may have an acidic group, and at least a part of the acidic group may be neutralized. Preferably, the monomer is partially neutralized with an alkaline substance such as sodium hydroxide, potassium hydroxide, or ammonium hydroxide.
[0040] At this time, the neutralization degree of the monomer may be 40 to 95 mol%, or 40 to 80 mol%, or 45 to 75 mol%. The range of the neutralization degree varies depending on the final properties, but if the neutralization degree is too high, the neutralized monomer precipitates and the polymerization is not smoothly carried out, and conversely, if the neutralization degree is too low, the water absorption ability of the polymer is greatly reduced and the polymer may exhibit properties similar to elastic rubber, which are difficult to handle.
[0041] The term "internal crosslinking agent" is used to distinguish it from the "surface crosslinking agent" for crosslinking the surface of the base resin, and plays a role in crosslinking the unsaturated bonds of the acrylic monomers described above to polymerize them. The crosslinking in this step is performed without distinction between the surface and the inside, but the surface of the superabsorbent resin particles finally produced by the surface crosslinking process of the base resin described below has a structure crosslinked by the surface crosslinking agent, and the inside has a structure crosslinked by the internal crosslinking agent.
[0042] As the internal crosslinking agent, any compound can be used as long as it enables the introduction of crosslinking bonds during polymerization of the acrylic acid monomer. Non-limiting examples of the internal crosslinking agent include N,N'-methylenebisacrylamide, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerin tri(meth)acrylate, pentaerythritol tetraacrylate, triallylamine, allyl (meth)acrylate, ethylene glycol diglycidyl ether, propylene glycol, glycerin, and ethylene carbonate. These crosslinking agents may be used alone or in combination.
[0043] The internal crosslinking agent is added at a concentration of 0.001 to 1% by weight, or 0.01 to 0.8% by weight, or 0.1 to 0.7% by weight relative to the monomer composition. That is, if the concentration of the internal crosslinking agent is too low, the water absorption speed of the resin may decrease and the gel strength may weaken, which is not preferable. Conversely, if the concentration of the internal crosslinking agent is too high, the water absorption power of the resin may decrease, which is not preferable as a water absorbent.
[0044] In addition, the base resin may further contain additives such as a thickener, a plasticizer, a storage stabilizer, and an antioxidant, if necessary.
[0045] The highly water-absorbent resin includes a surface cross-linked layer formed on the surface of the base resin, in which the cross-linked polymer is additionally cross-linked via a surface cross-linking agent.
[0046] Here, the aminoacetate-based chelating agent and cysteine are each independently contained in the inside of the surface cross-linked layer or on the surface of the surface cross-linked layer, which may mean that the aminoacetate-based chelating agent and cysteine are each independently added after polymerization of the base resin (=before the surface cross-linking step), during the surface cross-linking step, or after the surface cross-linking step, which will be described in more detail in the method for producing a superabsorbent polymer composition described later.
[0047] The surface cross-linked layer is formed by additionally cross-linking a cross-linked polymer via a surface cross-linking agent. In this case, the surface cross-linking agent is not particularly limited as long as it is a compound capable of reacting with a functional group of a polymer as a surface cross-linking agent generally used for surface cross-linking of a highly water-absorbent resin.
[0048] Preferably, in order to improve the properties of the resulting superabsorbent resin, the surface crosslinking agent can be one or more selected from the group consisting of polyhydric alcohol compounds; epoxy compounds; polyamine compounds; haloepoxy compounds; condensation products of haloepoxy compounds; oxazoline compounds; mono-, di- or polyoxazolidinone compounds; cyclic urea compounds; polyvalent metal salts; and alkylene carbonate compounds.
[0049] Specifically, examples of the polyhydric alcohol compound that can be used include one or more selected from the group consisting of mono-, di-, tri-, tetra- or polyethylene glycol, monopropylene glycol, 1,3-propanediol, dipropylene glycol, 2,3,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerol, polyglycerol, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,2-cyclohexanedimethanol.
[0050] In addition, as the epoxy compound, ethylene glycol diglycidyl ether, glycidol, etc. can be used, and as the polyamine compound, one or more selected from the group consisting of ethylenediamine, diethylenetriamine, triethylenetetraamine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine, and polyamidepolyamine can be used.
[0051] As the haloepoxy compound, epichlorohydrin, epibromohydrin, and α-methylepichlorohydrin can be used, while as the mono-, di-, or polyoxazolidinone compound, for example, 2-oxazolidinone can be used.
[0052] As the alkylene carbonate compound, ethylene carbonate can be used. These may be used alone or in combination with each other. On the other hand, in order to increase the efficiency of the surface cross-linking step, one or more of these surface cross-linking agents may be used together with one or more polyhydric alcohol compounds having 2 to 10 carbon atoms.
[0053] The content of the surface crosslinking agent to be added can be appropriately selected depending on the type of the surface crosslinking agent to be added and the reaction conditions, and generally, about 0.001 to about 5 parts by weight, preferably about 0.01 to about 3 parts by weight, and more preferably about 0.05 to about 2 parts by weight can be used relative to 100 parts by weight of the polymer.
[0054] If the content of the surface cross-linking agent is too low, the surface cross-linking reaction hardly occurs, whereas if the content exceeds 5 parts by weight per 100 parts by weight of the polymer, the surface cross-linking reaction proceeds excessively, which may result in a decrease in water absorption capacity and physical properties.
[0055] Meanwhile, the surface cross-linking agent may further include an inorganic substance. As the inorganic substance, one or more inorganic substances selected from the group consisting of silica, clay, alumina, silica-alumina composite, titania, zinc oxide, and aluminum sulfate may be used. The inorganic substance may be used in a powder form or a liquid form, and may be used, in particular, as an alumina powder, a silica-alumina powder, a titania powder, or a nanosilica solution. The inorganic substance may be used in an amount of about 0.001 to about 1 part by weight based on 100 parts by weight of the base resin.
[0056] In addition, the surface cross-linking agent may further include a thickener. In this way, by additionally cross-linking the surface of the base resin powder in the presence of a thickener, it is possible to minimize the deterioration of physical properties even after pulverization. Specifically, the thickener may be at least one selected from polysaccharides and hydroxy-containing polymers. As the polysaccharide, a gum-based thickener, a cellulose-based thickener, etc. may be used. Specific examples of the gum-based thickener include xanthan gum, gum arabic, karaya gum, tragacanth gum, ghatti gum, guar gum, locust bean gum, and psyllium seed gum, while specific examples of the cellulose-based thickener include hydroxypropylmethylcellulose, carboxymethylcellulose, methylcellulose, hydroxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, hydroxyethylmethylcellulose, hydroxymethylpropylcellulose, hydroxyethylhydroxypropylcellulose, ethylhydroxyethylcellulose, and methylhydroxypropylcellulose. On the other hand, specific examples of the hydroxy-containing polymer include polyethylene glycol and polyvinyl alcohol.
[0057] According to another embodiment of the invention, the superabsorbent resin composition may further include one or more additives selected from the group consisting of metal iodide salts, organic acids, and polyphenols, and the additives can further improve the deodorizing and odor preventing properties.
[0058] The metal iodide salt may be, for example, one or more selected from the group consisting of CuI, NaI, and KI, and I 2 The metal iodide salt can oxidize malodorous substances to impart a deodorizing property.
[0059] The organic acid may be, for example, one or more selected from the group consisting of citric acid, glutamic acid, ascorbic acid, benzoic acid, and erythorbic acid.
[0060] The polyphenol may be, for example, one or more selected from the group consisting of tannin, anthocyanin, flavonol, isoflavone, catechin, polyquercetin, and caffeic acid.
[0061] The additives are each independently contained in an amount, relative to 100 parts by weight of the base resin, of preferably 0.025 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, 2.5 parts by weight or less, 2.0 parts by weight or less, 1.5 parts by weight or less, or 0.01 to 2.5 parts by weight, 0.01 to 2.0 parts by weight, 0.025 to 2.5 parts by weight, 0.05 to 2.5 parts by weight, 0.05 to 2.0 parts by weight, 0.1 to 2.5 parts by weight, or 0.1 to 2.0 parts by weight.
[0062] When used within the above content range, a synergistic effect with cysteine can be realized, which is preferable.
[0063] On the other hand, if the metal iodide salt is contained in excess, there is a problem that the inherent physical properties of the superabsorbent resin are reduced, and the metal iodide salt is supplied as a solution in the process, which increases the amount of scum and reduces the deodorizing power. The metal iodide salt is mixed with the superabsorbent resin in the form of an aqueous solution using water as a solvent, and is present in the superabsorbent resin in a state where it is mixed and physically contained in the superabsorbent resin. The metal iodide salt solution may be a solution with a solids concentration of 1% or less.
[0064] Meanwhile, the additives are each independently contained in the inside of the surface cross-linked layer or on the surface of the surface cross-linked layer, which may mean that the additives are each independently added after polymerization of the base resin (=before the surface cross-linking step), during the surface cross-linking step, or after the surface cross-linking step, which will be described in more detail in the method for producing a superabsorbent polymer composition described later.
[0065] (Method of producing superabsorbent resin composition) According to one embodiment of the present invention, a method for producing a superabsorbent polymer composition is provided.
[0066] The method for producing the superabsorbent resin composition includes the steps of: The method includes a step (step 1) of cross-linking an acrylic acid monomer having at least a part of neutralized acidic groups in the presence of an internal cross-linking agent and a polymerization initiator to form a hydrogel polymer; a step (step 2) of preparing a base resin containing a cross-linked polymer by drying and pulverizing the hydrogel polymer; a step (step 3) of mixing a surface cross-linking composition with the base resin to prepare a mixture; and a step (step 4) of heat-treating the mixture to prepare a superabsorbent resin having a surface cross-linked layer formed on the surface of the base resin. The aminoacetate chelating agent and cysteine are mixed independently in the steps 2 to 4 and at least one of the steps before and after these steps.
[0067] The method for producing the superabsorbent polymer composition can effectively control odors caused by various factors without reducing the basic physical properties of the superabsorbent polymer, that is, water absorption and water retention, by using a combination of an aminoacetate chelating agent and cysteine. The aminoacetate chelating agent and cysteine can be used in the same manner as described above.
[0068] Meanwhile, "mixed in step A" means that the target mixture is additionally mixed while step A is being performed, and may mean that the target mixture is mixed in one or more divided portions to meet the desired content ratio in that step. Meanwhile, "mixed before or after step A" means that the target mixture is additionally mixed before step A is performed or after step A is completed.
[0069] More specifically, the aminoacetate-based chelating agent and cysteine are mixed independently in at least one of steps 2 to 4 and steps before and after these steps, which may mean mixing during the surface cross-linking step, before the surface cross-linking step, or after the surface cross-linking step is completed, and are mixed in at least one of these steps. The two additives are contained in the inside of the surface cross-linked layer or on the surface of the surface cross-linked layer, and thus have excellent deodorizing power by reacting with odor-generating substances, and can effectively suppress the generation of additional odor by inhibiting the growth of bacteria. On the other hand, if the two additives are mixed in the polymerization step, it may be difficult to achieve the desired effect.
[0070] More preferably, the aminoacetate-based chelating agent is mixed in step 2 or after step 4. More specifically, when the chelating agent is included in the step of preparing a base resin from a polymerized hydrogel polymer (step 2), this may mean that the chelating agent is mixed with the base resin and then added and mixed in the drying and grinding step. In this case, the chelating agent is included inside the surface cross-linked layer formed in the surface cross-linking step. Also, when the chelating agent is mixed after the surface cross-linking step (step 4), this may mean that the chelating agent is mixed together with the superabsorbent resin on which the surface cross-linked layer is formed. In this case, the chelating agent is included on the surface of the surface cross-linked layer formed in the surface cross-linking step.
[0071] More preferably, the cysteine is mixed after step 4. Specifically, when the cysteine is mixed after the surface cross-linking step (step 4), it may mean that the cysteine is mixed together with the superabsorbent resin on which a surface cross-linked layer is formed. In this case, the chelating agent is included on the surface of the surface cross-linked layer formed in the surface cross-linking step. When the cysteine is added after the surface cross-linking step (step 4), it may be advantageous in that the deodorizing power is improved by being present on the surface of the superabsorbent resin and increasing the contact area with the malodor.
[0072] According to one embodiment of the present invention, the method for producing the superabsorbent resin may further include one or more additives selected from the group consisting of metal iodide salts, organic acids, and polyphenols, and the additive components may be the same as those described above.
[0073] The additive is mixed in at least one of steps 2 to 4 and steps before and after these, which may mean mixing during the surface cross-linking step, before the surface cross-linking step, or after the surface cross-linking step is completed, and is mixed in at least one of these steps. As a result, the additive is contained in the inside of the surface cross-linked layer or on the surface of the surface cross-linked layer, and the generation of malodor can be more effectively suppressed.
[0074] More preferably, when the additive is added after the surface cross-linking step (step 4), it may be mixed with the superabsorbent resin having a surface cross-linked layer formed thereon. In this case, it may be advantageous in that the additive is present on the surface of the surface cross-linked layer formed in the surface cross-linking step, increasing the contact area with the odor, thereby improving the deodorizing power.
[0075] Each step of the present invention will now be described in detail.
[0076] (Stage 1) The step 1 is a step of preparing a hydrogel polymer, specifically, a step of cross-linking a monomer composition including an acrylic acid monomer having at least a partially neutralized acid group to form a hydrogel polymer.
[0077] The acrylic acid-based monomer may be any monomer that is commonly used in the manufacture of superabsorbent resins. Specifically, the acrylic acid-based monomer may be the same as described above.
[0078] The monomer composition also contains a polymerization initiator that is generally used in the production of highly water-absorbent resins.
[0079] The polymerization initiator may be a thermal polymerization initiator or a photopolymerization initiator depending on the polymerization method. However, since a certain amount of heat is generated by irradiation with ultraviolet light, etc., even in the photopolymerization method, and a certain amount of heat is generated by the progress of the polymerization reaction, which is an exothermic reaction, a thermal polymerization initiator may be additionally included.
[0080] The photopolymerization initiator may be, for example, one or more compounds selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyl alkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine, and alpha-aminoketone. A specific example of the acylphosphine is commercially available lucirin TPO, i.e., 2,4,6-trimethyl-benzoyl-trimethyl phosphine oxide. More various photopolymerization initiators are disclosed in Reinhold Schwalm's "UV Coatings: Basics, Recent Developments and New Application (Elsevier, 2007)" on page 115, which may be referred to.
[0081] The thermal polymerization initiator may be one or more compounds selected from the group consisting of persulfate initiators, azo initiators, hydrogen peroxide, and ascorbic acid. Specifically, the persulfate initiator may be sodium persulfate (Na 2 S 2 O 8 ), potassium persulfate (K 2 S 2 O 8 ), Ammonium persulfate ((NH 4 ) 2 S 2 O 8) are some examples. In addition, examples of azo initiators include 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, 2-(carbamoylazo)isobutylonitrile, 2,2-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 4,4-azobis-(4-cyanovaleric acid), Examples of thermal polymerization initiators include aryl ethers such as aryl ethers, aryl ethers, and aryl ethers with aryl groups. More various thermal polymerization initiators are disclosed in "Principle of Polymerization" by Odian (Wiley, 1981), page 203, which can be referred to.
[0082] Such a polymerization initiator is added at a concentration of 0.001 to 1% by weight, or 0.005 to 0.1% by weight, based on the monomer composition. That is, if the concentration of the polymerization initiator is too low, the polymerization rate is slowed down, and a large amount of residual monomers may be extracted in the final product, which is not preferable. On the other hand, if the concentration of the polymerization initiator is too high, the polymer chains forming the network are shortened, the content of water-soluble components is increased, and the physical properties of the resin, such as the water absorption capacity under pressure, may be reduced, which is not preferable.
[0083] Meanwhile, the polymerization of the monomer composition is carried out in the presence of an internal crosslinking agent in order to improve the physical properties of the resin obtained by the polymerization of the acrylic acid-based monomer. The internal crosslinking agent may be the same as that described above.
[0084] In addition, the cross-linking polymerization of the monomer composition is carried out in the presence of a foaming agent depending on the necessity and degree of improvement of the water absorption rate. The foaming agent is decomposed during the cross-linking polymerization reaction to generate gas, which can form pores in the hydrogel polymer. As a result, when the foaming agent is additionally used, a more developed porous structure is formed in the superabsorbent resin, and the water absorption rate of the superabsorbent resin can be further improved.
[0085] Non-limiting examples of the foaming agent include sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, calcium bicarbonate, calcium carbonate, magnesium bicarbonate, magnesium carbonate, azodicarbonamide (ADCA), dinitroso pentamethylene tetramine (DPT), p,p'-oxybis(benzenesulfonyl hydrazide (OBSH), p-toluenesulfonyl hydrazide (TSH), sucrose stearate (SSC ... The composition may include one or more compounds selected from the group consisting of sucrose stearate, sucrose palmitate, and sucrose laurate.
[0086] The blowing agent may be present in the monomer composition in an amount of 1000 to 4000 ppmw, more specifically, in an amount of 1000 ppm or more, alternatively 1100 ppmw or more, alternatively 1200 ppmw or more; and 4000 ppmw or less, alternatively 3500 ppmw or less, alternatively 3000 ppmw or less.
[0087] In addition, the monomer composition may further contain additives such as a thickener, a plasticizer, a storage stabilizer, and an antioxidant, if necessary.
[0088] The monomer composition is prepared in the form of a solution in which raw materials such as the acrylic acid monomer, the polymerization initiator, the internal crosslinking agent, and the foaming agent are dissolved in a solvent.
[0089] In this case, the solvent that can be used is not limited in composition as long as it can dissolve the above-mentioned raw materials. For example, the solvent may be water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, N,N-dimethylacetamide, or a mixture thereof.
[0090] The formation of the hydrogel polymer by polymerization of the monomer composition is carried out by a conventional polymerization method, and the process is not particularly limited.
[0091] As a non-limiting example, the polymerization method can be roughly divided into thermal polymerization and photopolymerization depending on the type of polymerization energy source. When the thermal polymerization is carried out, it is carried out in a reactor having a stirring shaft such as a kneader, and when the photopolymerization is carried out, it is carried out in a reactor equipped with a movable conveyor belt.
[0092] As an example, the monomer composition is charged into a reactor such as a kneader equipped with an agitator shaft, and hot air is supplied thereto or the reactor is heated to thermally polymerize the monomer composition, thereby obtaining a hydrogel polymer. At this time, depending on the type of the agitator shaft equipped in the reactor, the hydrogel polymer discharged from the outlet of the reactor is obtained as particles of several millimeters to several centimeters in size. Specifically, the obtained hydrogel polymer is obtained in various forms depending on the concentration of the monomer composition injected and the injection speed, but usually, a hydrogel polymer having a (weight average) particle size of 2 to 50 mm is obtained.
[0093] As another example, when the photopolymerization of the monomer composition is carried out in a reactor equipped with a movable conveyor belt, a sheet-like hydrogel polymer is obtained. In this case, the thickness of the sheet varies depending on the concentration and injection speed of the monomer composition to be injected, but it is generally preferable to adjust the thickness to 0.5 to 10 cm in order to ensure the production speed while allowing the entire sheet to be evenly polymerized.
[0094] The hydrogel polymer formed in this manner may have a water content of 40 to 80% by weight. Here, the water content is the weight of water in the total weight of the hydrogel polymer, and may be a value obtained by subtracting the weight of the polymer in a dry state from the weight of the hydrogel polymer. Specifically, it is defined as a value calculated by measuring the weight loss due to evaporation of water in the polymer during the process of drying by increasing the temperature of the polymer using infrared heating. At this time, the drying conditions are a method of increasing the temperature from room temperature to about 180°C and then maintaining it at 180°C, and the total drying time is set to 20 minutes, including a 5-minute temperature increase step.
[0095] (Stage 2) Step 2 of the present invention is to prepare a base resin by drying and pulverizing the hydrogel polymer prepared in step 1.
[0096] Specifically, the above step not only increases the drying efficiency of the hydrogel polymer, but also affects the morphology of the superabsorbent polymer, thereby affecting various physical properties of the superabsorbent polymer, including the water absorption rate, and in particular, in order to improve the water absorption rate of the superabsorbent polymer, the present invention may further include a step of coarsely pulverizing the hydrogel polymer before drying. Hereinafter, for the purpose of distinction from pulverization after drying, the term "coarse pulverization" is used in this specification for the purpose of convenience in referring to pulverization before drying.
[0097] The crusher used for the crushing is not limited in configuration, and specifically may include any one selected from the group of crushing devices consisting of a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a chopper, and a disc cutter, but is not limited to the above examples.
[0098] In this case, the coarse pulverization step can be performed so that the hydrogel polymer has a particle size of about 2 mm to about 10 mm. It is technically difficult to pulverize the hydrogel polymer to a particle size of less than 2 mm due to the high water content of the hydrogel polymer, and the pulverized particles may aggregate with each other. On the other hand, if the hydrogel polymer is pulverized to a particle size of more than 10 mm, the efficiency of the subsequent drying step may be increased only slightly.
[0099] The drying is carried out at a temperature of 120 to 250°C, 140 to 200°C, or 150 to 190°C. Here, the drying temperature is defined as the temperature of the heat medium supplied for drying, or the temperature inside the drying reactor containing the heat medium and the polymer in the drying process. If the drying temperature is low and the drying time is long, the process efficiency decreases, so in order to prevent this, the drying temperature is preferably 120°C or more. In addition, if the drying temperature is higher than necessary, the surface of the hydrogel polymer is excessively dried, which increases the generation of fine powder in the subsequent pulverization step and may deteriorate the physical properties of the final resin. In order to prevent this, the drying temperature is preferably 250°C or less.
[0100] At this time, the drying time in the drying step is not particularly limited, but can be adjusted to 20 to 90 minutes at the drying temperature in consideration of process efficiency and the physical properties of the resin.
[0101] The drying is carried out using a common medium, for example, by supplying hot air to the pulverized hydrogel polymer, irradiating it with infrared rays, irradiating it with ultrashort waves, or irradiating it with ultraviolet rays.
[0102] It is preferable that the drying is performed so that the dried polymer has a moisture content of 0.1 to 10% by weight. That is, if the moisture content of the dried polymer is less than 0.1% by weight, it is not preferable because excessive drying may increase the production cost and may cause degradation of the crosslinked polymer. If the moisture content of the dried polymer is more than 10% by weight, it is not preferable because defects may occur in the subsequent process.
[0103] Next, the dried hydrogel polymer can be pulverized. This is a step for optimizing the surface area of the base resin and the superabsorbent resin. The pulverization is carried out so that the particle size of the pulverized polymer is 150 to 850 μm.
[0104] In this case, the crushing machine that can be used may be a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, a jog mill, or any other conventional crushing machine.
[0105] In addition, in order to control the physical properties of the superabsorbent resin to be manufactured as a final product, a step of selectively classifying the polymer particles obtained by the pulverization step into particles having a particle size of 150 to 850 μm may be carried out.
[0106] The base resin can be obtained through the above classification steps. Such a base resin can have a particle size of 150 to 850 μm and can contain 2% by weight or less, or 1% by weight or less, of fine powder having a particle size of less than 150 μm.
[0107] Meanwhile, as described above, the aminoacetate-based chelating agent is included in the step (step 2) of preparing the base resin from the polymerized hydrogel polymer, which is advantageous in that it prevents the base resin from clumping, suppresses deterioration of physical properties, and allows the chelating agent to be distributed more uniformly. Meanwhile, the method of mixing the aminoacetate-based chelating agent is not particularly limited, and it may be mixed by a simple mixing method or a spraying method in the form of an aqueous solution.
[0108] (Stages 3 and 4) Step 3 of the present invention is a step of mixing a surface cross-linking composition with the base resin prepared in step 2, and step 4 is a step of heat-treating the mixture to prepare a superabsorbent resin having a surface cross-linked layer formed on the surface of the base resin.
[0109] The surface cross-linking composition used in step 3 includes a surface cross-linking agent. The surface cross-linking agent is not particularly limited as long as it is a compound that can react with a functional group of a polymer and is a surface cross-linking agent generally used for surface cross-linking of a superabsorbent resin.
[0110] Preferably, in order to improve the properties of the resulting superabsorbent resin, the surface crosslinking agent can be one or more selected from the group consisting of polyhydric alcohol compounds; epoxy compounds; polyamine compounds; haloepoxy compounds; condensation products of haloepoxy compounds; oxazoline compounds; mono-, di- or polyoxazolidinone compounds; cyclic urea compounds; polyvalent metal salts; and alkylene carbonate compounds.
[0111] Specifically, examples of the polyhydric alcohol compound that can be used include one or more selected from the group consisting of mono-, di-, tri-, tetra- or polyethylene glycol, monopropylene glycol, 1,3-propanediol, dipropylene glycol, 2,3,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerol, polyglycerol, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,2-cyclohexanedimethanol.
[0112] In addition, as the epoxy compound, ethylene glycol diglycidyl ether, glycidol, etc. can be used, and as the polyamine compound, one or more selected from the group consisting of ethylenediamine, diethylenetriamine, triethylenetetraamine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine, and polyamidepolyamine can be used.
[0113] As the haloepoxy compound, epichlorohydrin, epibromohydrin, and α-methylepichlorohydrin can be used, while as the mono-, di-, or polyoxazolidinone compound, for example, 2-oxazolidinone can be used.
[0114] As the alkylene carbonate compound, ethylene carbonate can be used. These may be used alone or in combination with each other. On the other hand, in order to increase the efficiency of the surface cross-linking step, one or more of these surface cross-linking agents may be used together with one or more polyhydric alcohol compounds having 2 to 10 carbon atoms.
[0115] The content of the surface crosslinking agent to be added can be appropriately selected depending on the type of the surface crosslinking agent to be added and the reaction conditions, and generally, about 0.001 to about 5 parts by weight, preferably about 0.01 to about 3 parts by weight, and more preferably about 0.05 to about 2 parts by weight can be used relative to 100 parts by weight of the polymer.
[0116] If the content of the surface cross-linking agent is too low, the surface cross-linking reaction hardly occurs, whereas if the content exceeds 5 parts by weight per 100 parts by weight of the polymer, the surface cross-linking reaction proceeds excessively, which may result in a decrease in water absorption capacity and physical properties.
[0117] Meanwhile, the surface cross-linking composition may be used in a step of forming a surface cross-linked layer by additionally adding an inorganic material. As the inorganic material, one or more inorganic materials selected from the group consisting of silica, clay, alumina, silica-alumina composite, titania, zinc oxide, and aluminum sulfate may be used. The inorganic material may be used in a powder form or a liquid form, and may be used, in particular, as an alumina powder, a silica-alumina powder, a titania powder, or a nanosilica solution. The inorganic material may be used in an amount of about 0.001 to about 1 part by weight based on 100 parts by weight of the base resin.
[0118] In addition, the surface cross-linking composition may further include a thickener. In this way, by additionally cross-linking the surface of the base resin powder in the presence of a thickener, it is possible to minimize the deterioration of physical properties even after pulverization. Specifically, the thickener may be one or more selected from polysaccharides and hydroxy-containing polymers. As the polysaccharide, a gum-based thickener, a cellulose-based thickener, etc. may be used. Specific examples of the gum-based thickener include xanthan gum, gum arabic, karaya gum, tragacanth gum, ghatti gum, guar gum, locust bean gum, and psyllium seed gum, while specific examples of the cellulose-based thickener include hydroxypropylmethylcellulose, carboxymethylcellulose, methylcellulose, hydroxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, hydroxyethylmethylcellulose, hydroxymethylpropylcellulose, hydroxyethylhydroxypropylcellulose, ethylhydroxyethylcellulose, and methylhydroxypropylcellulose. On the other hand, specific examples of the hydroxy-containing polymer include polyethylene glycol and polyvinyl alcohol.
[0119] On the other hand, the method of mixing the surface cross-linking composition with the base resin is not particularly limited as long as the method can uniformly mix them with the base resin, and can be appropriately adopted and used.
[0120] For example, a method in which the surface crosslinking composition is placed in a reaction tank and the base resin is mixed, a method in which a surface crosslinking composition is sprayed onto the base resin, a method in which the base resin and the surface crosslinking composition are continuously supplied to a continuously operated mixer and mixed therewith, and the like are used.
[0121] At this time, the surface crosslinking composition may be a solution, and when the content of solids in the solution is 1 wt% or more, 3 wt% or more, 5 wt% or more, 10 wt% or more, or 50 wt% or less, 30 wt% or less, or 20 wt% or less, it is suitable for uniform dispersion in the base resin and at the same time, the clumping phenomenon of the base resin can be prevented.
[0122] Next, the step 4 is a step of heat-treating the mixture to produce a superabsorbent resin having a surface cross-linked layer formed on the surface of the base resin, specifically, a step of heat-treating the base resin and the surface cross-linking composition to form an interpenetrating polymer network on the surface of the cross-linked polymer contained in the base resin to further improve the physical properties of the superabsorbent resin. By such surface modification, a surface cross-linked layer is formed on the surface of the pulverized base resin particles.
[0123] The formation of the surface cross-linked layer is carried out by a conventional method for increasing the cross-linking density of the polymer particle surface, for example, by mixing a surface cross-linking agent composition solution containing a surface cross-linking agent with the pulverized polymer, and heat-treating the mixture to cause a cross-linking reaction.
[0124] The step 4 is carried out at a temperature of about 80° C. to about 250° C. More specifically, the surface cross-linking process is carried out at a temperature of about 100° C. to about 220° C., or about 110° C. to about 200° C., or about 120° C. to about 190° C., for about 10 minutes to about 2 hours, or about 20 minutes to about 60 minutes. If the cross-linking reaction temperature is less than 160° C. or the reaction time is too short, the surface cross-linking reaction does not proceed well and the permeability is reduced, whereas if the temperature is more than 200° C. or the reaction time is too long, the water retention capacity is reduced.
[0125] The temperature raising means for the surface crosslinking reaction is not particularly limited. Heating can be performed by supplying a heat medium or directly supplying a heat source. At this time, the type of heat medium that can be used can be a heated fluid such as steam, hot air, hot oil, etc., but the present invention is not limited to these, and the temperature of the heat medium to be supplied can be appropriately selected in consideration of the means of the heat medium, the heating rate, and the target temperature of the heat raising. On the other hand, the heat source to be directly supplied can be exemplified by heating by electricity and heating by gas, but the present invention is not limited to the above-mentioned examples.
[0126] Meanwhile, as described above, the aminoacetate-based chelating agent is mixed after the step (step 4) of producing a superabsorbent resin having a surface cross-linked layer formed on the surface of the base resin by heat-treating the mixture, which is advantageous in that it can further reduce the possibility of scum generation during processing after surface cross-linking with cysteine, etc. Meanwhile, the method of mixing the aminoacetate-based chelating agent is not particularly limited, and it can be mixed by a simple mixing method or a spraying method in the form of an aqueous solution.
[0127] In addition, as described above, cysteine is mixed after the step (step 4) of producing a superabsorbent resin having a surface cross-linked layer formed on the surface of the base resin by heat-treating the mixture, and is advantageous in that it is present on the surface of the superabsorbent resin and increases the contact area with the odor, thereby improving the deodorizing power. Meanwhile, the method of mixing cysteine is not particularly limited, and it can be mixed by spraying it in an aqueous solution state or by dry mixing.
[0128] Also, as described above, one or more additives selected from the group consisting of metal iodide salts, organic acids, and polyphenols may be mixed after the step (step 4) of heat-treating the mixture to prepare a superabsorbent resin having a surface cross-linked layer formed on the surface of the base resin, which is advantageous in that the additives are present on the surface of the superabsorbent resin and increase the contact area with the odor, thereby improving the deodorizing power. Meanwhile, the additives are not particularly limited, and may be mixed by spraying in the form of an aqueous solution or by dry mixing.
[0129] According to one embodiment of the present invention, after the step of preparing a superabsorbent resin having a surface cross-linked layer formed on the surface of the base resin (step 4), a step of mixing an aminoacetate-based chelating agent, cysteine, metal iodide salt, organic acid and polyphenol in the form of an aqueous solution (water addition step) may be included, in which case a drying step is additionally performed. The above-mentioned content can be applied to the drying process in the same manner.
[0130] Preferred examples are presented below for better understanding of the present invention. However, the following examples are merely for illustrating the present invention and are not intended to limit the present invention thereto.
[0131] Examples and Comparative Examples: Production of Superabsorbent Resin Example 1 (Step 1) 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer solution composition having a monomer concentration of 45.8 wt%. The aqueous monomer solution composition was fed into the feed section of a polymerization vessel equipped with a continuously moving conveyor belt, and then irradiated with ultraviolet light using a UV irradiation device (irradiation dose: 10 mW / cm) while maintaining the polymerization atmosphere temperature at 80°C. 2 ) and UV polymerization was allowed to proceed for 2 minutes to produce a hydrogel polymer.
[0132] (Step 2) The hydrogel polymer was transferred to a meat chopper and cut into pieces of 2 mm to 10 mm. At this time, the water content of the cut hydrogel polymer was 47% by weight. Next, the hydrogel polymer was dried in a hot air dryer at a temperature of 170°C for 30 minutes, and the dried hydrogel polymer was pulverized in a pin mill pulverizer. Next, the polymer with a particle size (average particle size) of 150 μm to 850 μm was classified using a sieve to produce a base resin.
[0133] After (Step 3), 100 parts by weight of the prepared base resin was evenly mixed with a surface cross-linking liquid (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S), and 0.1 parts by weight of silica (Aerosil A200)).
[0134] (Step 4) Next, the mixture was subjected to a surface cross-linking reaction at 140° C. for 30 minutes. After the surface treatment was completed, a superabsorbent resin having an average particle size of 150 to 850 μm was obtained using a sieve. In the superabsorbent resin thus obtained, the content of particles having an average particle size of less than 150 μm was less than 2%.
[0135] In step 2, 0.5 parts by weight of EDTA (based on 100 parts by weight of base resin) as an aminoacetate-based chelating agent was dissolved in an aqueous solution and mixed with the base resin by spraying.
[0136] In addition, after the surface cross-linking step in step 4, 0.2 parts by weight of L-cysteine (based on 100 parts by weight of base resin) was dissolved in an aqueous solution and mixed with the superabsorbent resin by spraying. Then, a drying step was performed to prepare a superabsorbent resin composition.
[0137] Examples 2 to 17 and Comparative Examples 1 to 3 A highly water-absorbent resin was produced in the same manner as in Example 1, except that the components and contents of the additives were changed as shown in Table 1 when the additives were added.
[0138] Meanwhile, in Examples 9 to 11, additional additives were sprayed onto the surface-crosslinked superabsorbent resin in the form of aqueous solutions (metal iodide salt solution (concentration 1%, CuI), tannin solution, citric acid solution), and an additional drying step was performed.
[0139] [Table 1A] [Table 1B]
[0140] Experimental Example The superabsorbent resin compositions prepared in the above Examples and Comparative Examples were measured for various physical properties by the following methods.
[0141] (1) Water absorption property evaluation 1) Centrifuge Retention Capacity (CRC) The water retention capacity of the superabsorbent resin compositions of the Examples and Comparative Examples was measured in terms of the water absorption capacity under no load according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP241.3.
[0142] Specifically, the highly water-absorbent resin compositions obtained in the Examples and Comparative Examples were classified using sieves of #30-50 to obtain resin W. 0 (g) (about 0.2 g) was uniformly placed in a nonwoven envelope, sealed, and then immersed in physiological saline (0.9 wt%) at room temperature. After 30 minutes, the water was removed from the envelope at 250 G for 3 minutes using a centrifuge, and the mass of the envelope W 2 The mass W (g) was measured after the same procedure was performed without using the resin. 1 (g) was measured.
[0143] Using the obtained masses, the CRC (g / g) was calculated according to the following formula 1.
[0144] [Formula 1] CRC(g / g) = {[W 2 (g)-W 1 (g)] / W 0 (g)}-1
[0145] 2) Absorbency under Pressure (AUP) The water absorbency at a pressure of 0.7 psi of each of the superabsorbent resin compositions of the above Examples and Comparative Examples was measured by EDANA method WSP242.3.
[0146] First, when measuring the pressurized water absorption capacity, the resin-classified powder used in the CRC measurement was used.
[0147] Specifically, a 400-mesh stainless steel wire mesh was attached to the bottom of a plastic cylinder with an inner diameter of 25 mm. 0 The piston that can uniformly apply a load of 0.7 psi to the surface of the cylinder is slightly smaller than 25 mm in outer diameter, has no gap with the inner wall of the cylinder, and is not hindered from moving up and down. At this time, the weight of the device is W 3 (g) was measured.
[0148] A glass filter with a diameter of 90 mm and a thickness of 5 mm was placed inside a petroleum dish with a diameter of 150 mm, and physiological saline solution consisting of 0.9% by weight of sodium chloride was placed at the same level as the upper surface of the glass filter. A sheet of filter paper with a diameter of 90 mm was placed on top of the glass filter. The measuring device was placed on the filter paper, and the liquid was absorbed under a load for one hour. After one hour, the measuring device was lifted up and its weight W 4 The mass (g) was measured. The obtained masses were used to calculate the water absorption capacity under pressure (g / g) according to the following formula 2.
[0149] [Formula 2] AUP(g / g) = [W 4 (g)-W 3 (g)] / W 0 (g)
[0150] (2) Evaluation of bacterial inhibition rate The bacteria inhibition rates of the superabsorbent resin compositions of the above Examples and Comparative Examples were evaluated by the following method.
[0151] Specifically, Escherichia coli (ATCC25922) test bacteria were cultured in LB-Broth for 24 hours, and the cultured bacteria were then diluted and injected into 2 g of each sample of the superabsorbent polymer composition together with artificial urine. After culturing at 37°C for 24 hours, the bacteria were extracted and the bacterial count was measured (average value of two samples).
[0152] Bacteria suppression rate (%) = (1-((bacteria amount in sample) / (bacteria amount in reference sample (sample with no deodorant effect))) x 100 (%)
[0153] The experimental results of the bacteria inhibition rate are shown in Table 2. The values in Table 2 show the deodorizing efficiency in comparison with Comparative Example 1, and the higher the deodorizing efficiency, the higher the value.
[0154] (3) Deodorizing power (odor removal rate) The deodorizing power was measured using an adsorption tube method. The odorous substances ketone (diacetyl), sulfur compound (dimethyl trisulfide), and aldehyde (3-methyl butanal) were selected and tested for their deodorizing power.
[0155] - Adsorption tube measurement method: 1g of super absorbent resin was placed in a 500mL glass bottle, and 25mL of odorous substances were poured into it. After that, aging was carried out for 3 hours in a thermostatic chamber, and then collection was carried out for 20 minutes. At this time, the temperature of the thermostatic chamber was 35 degrees, and the N2 flow rate was 250mL / min. The odors that floated around were then adsorbed into the connected adsorption tube, and this was repeated twice for the same sample. The collection results were analyzed by GC and the results were confirmed.
[0156] - Deodorizing power (%) = (Amount of odor of reference sample (sample without deodorizing power) measured by GC - Amount of odor of sample measured by GC) / Amount of odor of reference sample (sample without deodorizing power) measured by GC x 100 (%)
[0157] The results of the deodorizing power experiment are shown in Table 2. The values in Table 2 show the deodorizing efficiency relative to Comparative Example 1, with the higher the value being, the higher the deodorizing efficiency.
[0158] [Table 2]
[0159] As can be seen from the results in Table 2, the superabsorbent polymer composition according to the embodiment of the present invention exhibits excellent water absorption properties due to the use of a combination of an aminoacetate chelating agent and cysteine, while at the same time having excellent deodorizing and anti-odor properties, and can effectively inhibit the growth of bacteria that occurs during the wear of the product.
[0160] It was confirmed that in the comparative example, where only one of the two additives was used, it was difficult to simultaneously achieve both bacteria inhibition rate and deodorizing power. In particular, when a metal salt of ricinoleic acid, which is not an aminoacetate chelating agent, was used in combination with cysteine, the deodorizing power was similar to that of the examples, but the bacteria growth inhibition rate was significantly lower.
Claims
1. A superabsorbent resin comprising: a base resin containing a crosslinked polymer obtained by crosslinking an acrylic acid monomer having at least a partially neutralized acidic group with an internal crosslinking agent; and a surface crosslinked layer formed on the surface of the base resin, the surface crosslinked layer being further crosslinked with the crosslinked polymer via a surface crosslinking agent; Aminoacetate chelating agents; and cysteine; The aminoacetate-based chelating agent and cysteine are each independently contained inside the surface-crosslinked layer or on the surface of the surface-crosslinked layer. Super absorbent resin composition.
2. The aminoacetate chelating agent includes at least one selected from the group consisting of ethylenediaminetetraacetic acid (EDTA), L-glutamic acid diacetic acid (GLDA), methylglycine diacetic acid (MGDA), hydroxyethylethylenediaminetriacetic acid (HEDTA), ethanol diglycine acid (EDG), diethylenetriaminepentaacetic acid (DTPA), and salts thereof; The highly water-absorbent resin composition according to claim 1.
3. The aminoacetate-based chelating agent is contained in an amount of 0.01 to 3 parts by weight per 100 parts by weight of the base resin. The highly water-absorbent resin composition according to claim 1.
4. The cysteine is contained in an amount of 0.01 to 3 parts by weight based on 100 parts by weight of the base resin. The highly water-absorbent resin composition according to claim 1.
5. Further comprising one or more additives selected from the group consisting of metal iodide salts, organic acids, and polyphenols; The highly water-absorbent resin composition according to any one of claims 1 to 4.
6. Step 1: forming a hydrogel polymer by cross-linking and polymerizing an acrylic acid monomer having at least a part of neutralized acid groups in the presence of an internal cross-linking agent and a polymerization initiator; A step (step 2) of preparing a base resin containing a crosslinked polymer by drying and pulverizing the hydrogel polymer; mixing the base resin with a surface cross-linking composition to prepare a mixture (Step 3); and Step 4: heat-treating the mixture to produce a superabsorbent resin having a surface cross-linked layer formed on the surface of the base resin; The aminoacetate chelating agent and cysteine are mixed independently in at least one of steps 2 to 4 and steps before and after these steps. A method for producing a superabsorbent resin composition.
7. The aminoacetate chelating agent is mixed in step 2 or after step 4. A method for producing the highly water-absorbent resin composition according to claim 6.
8. The cysteine is mixed after step 4. A method for producing the highly water-absorbent resin composition according to claim 6.
9. The method further comprises mixing one or more additives selected from the group consisting of metal iodide salts, organic acids, and polyphenols. A method for producing the highly water-absorbent resin composition according to claim 6.
10. The additives are mixed independently in at least one of steps 2 to 4 and before and after these steps. A method for producing the highly water-absorbent resin composition according to claim 9.
11. The additives are each independently mixed after step 4. A method for producing the highly water-absorbent resin composition according to claim 9.
Citation Information
Patent Citations
Water absorbing agent, water absorbing article and method for production of water absorbing agent
JP2006297373A
Method for producing odor-resistant water-absorbing polymer particles
JP2012526878A
Superabsorbent resin composition
JP2021512967A
Water absorbent having water-absorbent resin as main component, and method for producing same
WO2020145384A1
Water-absorbing resin and manufacturing method for same
WO2021162085A1